2007
DOI: 10.1002/jor.20453
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated fracture healing in the geriatric, osteoporotic rat with recombinant human platelet‐derived growth factor‐bb and an injectable beta‐tricalcium phosphate/collagen matrix

Abstract: Aging and osteoporosis contribute to decreased bone mass and bone mineral density as well as compromised fracture healing rates and bone repair quality. Consequently, the purpose of this study was to determine if recombinant human platelet-derived growth factor-BB (rhPDGF-BB) delivered in an injectable beta-tricalcium phosphate/collagen matrix would enhance tibial fracture healing in geriatric (>2 years of age), osteoporotic rats. A total of 80 rats were divided equally among four groups: Fracture alone; Fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 29 publications
(34 reference statements)
2
91
0
2
Order By: Relevance
“…These findings support the hypothesis that rhPDGF-BB induced fracture callus cell proliferation and led to a subsequent increase in the structural properties of the callus in the diabetic rat. The findings of this study are supported by those reported by Hollinger et al, 40 in which rhPDGF-BB was found to accelerate fracture healing in geriatric, osteoporotic rats.…”
Section: Fracture Healing In a Diabetic Rat Modelsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings support the hypothesis that rhPDGF-BB induced fracture callus cell proliferation and led to a subsequent increase in the structural properties of the callus in the diabetic rat. The findings of this study are supported by those reported by Hollinger et al, 40 in which rhPDGF-BB was found to accelerate fracture healing in geriatric, osteoporotic rats.…”
Section: Fracture Healing In a Diabetic Rat Modelsupporting
confidence: 91%
“…[37][38][39] In addition, rhPDGF-BB treatment at doses used in this study significantly enhanced fracture healing in aged, osteopenic rats. 40 Fracture callus cell proliferation was significantly higher in the diabetic rats treated with rhPDGF-BB, indicating that rhPDGF-BB treatment can ameliorate the deficit in callus cell proliferation observed in diabetic animals ( Figs. 1 and 2).…”
Section: Fracture Healing In a Diabetic Rat Modelmentioning
confidence: 91%
“…A representative photograph for determination of these areas is shown in Fig. 2 Effects of HGF on bone healing b-TCP and collagen promotes healing of bone fractures after a tibial osteotomy, compared with the material without PDGF-BB [6]. In rabbits, FGF-2 in a mixture of b-TCP and collagen facilitates healing of segmental bone defects [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is highly likely that a combination of osteoinductive growth factors and scaffolds provides an appropriate osteoinductive environment for osteogenic cells. Promoting bone formation by applying polypeptide growth factors has been reported, including bone morphogenetic protein (BMP) [4], fibroblast growth factor-2 (FGF-2) [5], platelet-derived growth factor (PDGF) [6], and vascular endothelial cell growth factor (VEGF) [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation